Body mass index, physical activity, and risk of adult meningioma and glioma: A meta-analysis. (13th October 2015) - Niedermaier, Tobias; Behrens, Gundula; Schmid, Daniela; Schlecht, Inga; Fischer, Beate; Leitzmann, Michael F.
Abstract : Objective: Whether adiposity and lack of physical activity affect the risk for developing meningioma and glioma is poorly understood. Our objective was to characterize these associations in detail. Methods: We conducted a systematic review and meta-analysis of adiposity and physical activity in relation to meningioma and glioma using cohort and case-control studies published through February 2015. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: We identified 12 eligible studies of body mass index (BMI) and 6 studies of physical activity, comprising up to 2, 982 meningioma cases and 3, 057 glioma cases. Using normal weight as the reference group, overweight (summary relative risk [RR] = 1.21, 95% confidence interval [CI] = 1.01–1.43) and obesity (RR = 1.54, 95% CI = 1.32–1.79) were associated with increased risk of meningioma. In contrast, overweight (RR = 1.06, 95% CI = 0.94–1.20) and obesity (RR = 1.11, 95% CI = 0.98–1.27) were unrelated to glioma. Similarly, dose-response meta-analyses revealed a statistically significant positive association of BMI with meningioma, but not glioma. High vs low physical activity levels showed a modest inverse relation to meningioma (RR = 0.73, 95% CI = 0.61–0.88) and a weak inverse association with glioma (RR = 0.86, 95% CI = 0.76–0.97). Relations persisted when the data were restricted to prospective studies, except for the association between physical activity and glioma, which was rendered statistically nonsignificant (RR = 0.91, 95% CI = 0.77–1.07). Conclusions: Adiposity is related to enhanced risk for meningioma but is unassociated with risk for glioma. Based on a limited body of evidence, physical activity is related to decreased risk of meningioma but shows little association with risk of glioma.